1977
DOI: 10.1037/0033-2909.84.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Left-handedness.

Abstract: The phenomenon of left-handedness is reviewed from prehistoric man through contemporary studies of lateralization of cerebral function. The following conclusions seem warranted: Handedness is most appropriately regarded as a continuum ranging from strong right-handedness across mixed-handedness to strong left-handedness. Left-handedness, ranging from moderate through strongly lefthanded, is found in approximately 10% of the population. Evidence for a genetic basis of handedness remains positive, but with no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
193
4
13

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(232 citation statements)
references
References 119 publications
(189 reference statements)
22
193
4
13
Order By: Relevance
“…Hussain et al [11] showed 71.6 % cases presented with anterior bleed which is in concordance with our study (69.4 %). In the earlier studies by Joice et al [12] and Hardyck et al [13] no significant association was found between side of nasal bleeding and hand dominance but the present study showed highly significant (p = 0.001) association between right handedness and left sided nasal bleed.…”
Section: Discussioncontrasting
confidence: 61%
“…Hussain et al [11] showed 71.6 % cases presented with anterior bleed which is in concordance with our study (69.4 %). In the earlier studies by Joice et al [12] and Hardyck et al [13] no significant association was found between side of nasal bleeding and hand dominance but the present study showed highly significant (p = 0.001) association between right handedness and left sided nasal bleed.…”
Section: Discussioncontrasting
confidence: 61%
“…Psychophysiological studies support the hypothesis that visual input is lateralized and correlated with handedness (reviewed by Hardyck & Petrinovich, 1977). The reviewers suggest that lateralization of visual function is organized along a continuum of handedness.…”
Section: N Europhysiologicai Significancementioning
confidence: 91%
“…In adults, sex was found to be unrelated to stability of EEG asymmetry (Vuga et al, 2006). Handedness may be an important factor influencing stability due to the differential brain organization of left and right handed individuals (Galaburda et al, 1990;Hardyck & Petrinovich, 1977). In prior studies of frontal EEG asymmetry with children, handedness was either restricted to right-handers or ignored (Rybak et al, 2006;Santesso et al, 2006;Shankman et al, 2005).…”
Section: Introductionmentioning
confidence: 96%